THE IMPACT OF INFORMAL FAMILY EDUCATION ON CHILDREN'S SOCIAL AND EMOTIONAL SKILLS - Abdul Wahab Syakhrani; Aslan Aslan (CV. ADIBA AISHA AMIRA, 2024)
This study aims to examine the impact of informal education provided by families on children's social and emotional skills. Informal education includes daily interactions, guidance and support provided by parents and other family members. The results show that informal education in the family environment has a significant influence on children's social development, including communication, cooperation and conflict resolution skills. Children learn social norms and interpersonal skills through the example set by family members, which helps them establish harmonious and effective relationships. In addition to social aspects, informal education also plays an important role in children's emotional development. The emotional support and care provided by the family helps children feel safe and valued, which is important for their emotional health. Through parental guidance, children learn to recognize, express and manage their emotions. The family's role in encouraging children to explore their interests and talents also enhances children's self-confidence and self-esteem. Overall, this study underscores that informal education within the family provides a strong foundation for children's social and emotional development, better preparing them to face the challenges of life